2018
DOI: 10.1093/intqhc/mzy056
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing triage time: effects of implementing a step-wise ESI algorithm in an EHR†

Abstract: The computerized triage scale improved speed of triage, allowing more high acuity patients to be seen within recommended timeframes, without notable impact on quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…[ 13 ] Some studies indicated that the average duration of triage is 2.6 ± 2.5,[ 14 ] and 5.9 minutes. [ 15 ] In another study, it was found that the longest time period allocated for triage was in category three patients at 2.8 ± 2.5 min. [ 14 ] The literature suggests that triage assessment should be performed between 2 and 5 min in order for the assessment to be fast and accurate.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] Some studies indicated that the average duration of triage is 2.6 ± 2.5,[ 14 ] and 5.9 minutes. [ 15 ] In another study, it was found that the longest time period allocated for triage was in category three patients at 2.8 ± 2.5 min. [ 14 ] The literature suggests that triage assessment should be performed between 2 and 5 min in order for the assessment to be fast and accurate.…”
Section: Discussionmentioning
confidence: 99%
“…There are various approaches that aim to improve coordination of ED care by reducing time for triage, treatment and transfer of patients. [25][26][27][28] Our work suggests that ESI might be a promising tool to improve coordination of care by predicting type and amount of hospital beds required for specific ED patient groups. Patients with symptoms pointing at neurological problems need particular attention as ESI failed to sufficiently predict the care facility level needed in this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…One important result of our analysis was the discordance between ED-assigned acuity and ophthalmologyassigned acuity in patients with an ocular complaint as the primary diagnosis. ED-assigned acuity status can be used to derive quality statistics or set hospital policy regarding consultations 6,7 . Our data demonstrate that retrospective ophthalmology-assigned acuity was somewhat discordant from ED-assigned acuity, particularly on the extremes of the ED Severity Index.…”
Section: Discussionmentioning
confidence: 99%